Pregabalin-Induced Remission in a 62-Year-Old Woman with a 20-Year History of Vulvodynia - Laurence Jerome (Pain Research and Management)
A case of a 62-year-old woman presenting with a 20-year history of vulvodynia previously unresponsive to medical treatment is described. The epidemiology, phenomenology and medical management of vulvodynia is reviewed. The case presentation illustrates the role of pregabalin in successful medical management of this chronic pain disorder, as well as the management of common psychiatric morbidities associated with this condition.